سيكولوجية مهارة القراءة وتعليمها - Hasan Abidin; Hasan (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
Abstract: Education is a human effort to guide children to become adults and provide provisions to the nation's generation with various skills and abilities to live responsibly, so that it is hoped that the human mentality will change to survive. One of a child's tasks is to learn, whether it is academic, non-academic, and learning through experience. A child is never separated from the learning process both in the environment and at home. One way a person learns is by reading, reading is a necessary tool in all areas of life. Reading is an activity of seeing and understanding the contents of what is written by reading someone will know, predict, calculate, and understand what is written. Reading without understanding the content of the reading is an activity that will end in vain. Therefore, reading is not only a spelling and composing activity. Reading is a complex cognitive process for processing reading content, which aims to understand the author's ideas and messages and make them part of his knowledge. Reading is an activity that requires the regulation of cognitive abilities such as meaning and understanding symbols. In this day and age life is also increasingly modern, where all information obtained by the public is obtained from social media news or information from cyberspace. This shows the importance of humans having good reading skills, if many people cannot read properly and correctly this will hinder society from following technological advances today or in the future. Therefore, it is important for us to hone our reading skills.